Role of Speed Humps in Urban Road Safety: Perceptions, Health Risks, and Experimental Fuel Consumption Effects in a Secondary City in Ghana - Sumbo, Dennis Kamaanaa; Wulifan, Joseph Kwame; Bagson, Ernest (Transportation research record, 2025)
Speed humps (are becoming pervasive on urban roads of Africa and have become a subject matter of enquiry. This study contributes to this literature through the case of Wa, Ghana. Underpinned by the sustainable safety vision, the study utilized data in the form of qualitative texts, descriptive statistics, and fuel consumption data. Speed humps in Wa were enumerated and mapped, and the lived experiences of purposively selected vehicle users and pedestrians were recorded to understand their perceptions of speed humps in the realm of urban mobility. The study enumerated 148 speed humps that were unevenly distributed on different roads in Wa. A significant difference (−63%) in fuel economy in miles per gallon (mpg) between the hump-free sections and hump/post-hump sections of a 10-km trail was found, with an average consumption of 48.4 mpg (standard deviation [SD] = 10.4) in hump-free sections and 17.9 mpg (SD = 7.1) for hump/post-hump sections. On this basis, the average vehicle consumes 0.00166L due to a speed hump or 6L (GHS85) in a year, with 1000 vehicles consuming extra 6059L (GHS85, 000) and emit 15,147 kg of extra CO2 in a year due to the speed humps. Vehicle users and pedestrians, in particular, positively perceived the speed humps as offsetting the disregard for traffic regulations and frequent road crashes. However, pedestrians and vehicle users agreed that poorly designed and constructed speed humps in Wa posed a high risk to road users. The study concludes that most speed humps in Wa fall short of the sustainable safety vision principles. It is recommended that speed humps be standardized to improve safety, user friendliness, and general efficiency, and they should be viewed as a short- to medium-term measure to be subsequently replaced by more sustainable options, including a change in driving behavior and technology-based solutions that meet the criteria of the sustainable safety vision model.